2022
DOI: 10.3390/su14052512
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Mechanisms of Summer Thermal Environment of Waterfront Space in China’s Cold Regions

Abstract: Water is an essential part of the urban ecosystem and plays a vital role in alleviating urban heat island (UHI) problems. The contribution toward UHI mitigation made by bodies of water needs to be ascertained to establish waterfront thermal environment construction standards. In this study, the thermal environment of the waterfront space of Tianjin in the cold regions of China was the research object. Through a survey including 141 valid questionnaires and the field measurement of four typical waterfront space… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 64 publications
0
4
0
Order By: Relevance
“…With the deterioration of the urban thermal environment, it is urgent to explore more effective UHI mitigation measures to alleviate its impact on the environment and city residents [61]. Several studies have explored mitigation strategies for UHI, such as reducing man-made heat emissions [62][63][64], increasing urban green space and green infrastructure [65], increasing the water area [66], improving underlying surface materials [67,68], building high-albedo roofs and roads [69,70], urban planning [71], building green ecological roofs [72,73], etc. For example, Bustami et al [74] found that the continuous density and spread degree of urban development spaces were both key factors affecting the UHI effect, and maintained that urban continuity and more incongruous urban forms should be considered when designing mitigation strategies.…”
Section: Urban Heat Island Mitigation Measuresmentioning
confidence: 99%
“…With the deterioration of the urban thermal environment, it is urgent to explore more effective UHI mitigation measures to alleviate its impact on the environment and city residents [61]. Several studies have explored mitigation strategies for UHI, such as reducing man-made heat emissions [62][63][64], increasing urban green space and green infrastructure [65], increasing the water area [66], improving underlying surface materials [67,68], building high-albedo roofs and roads [69,70], urban planning [71], building green ecological roofs [72,73], etc. For example, Bustami et al [74] found that the continuous density and spread degree of urban development spaces were both key factors affecting the UHI effect, and maintained that urban continuity and more incongruous urban forms should be considered when designing mitigation strategies.…”
Section: Urban Heat Island Mitigation Measuresmentioning
confidence: 99%
“…In a review of the relevant literature on the impact of water bodies on the microclimate of waterfront settlements, the intensity of the cooling effect of a water body was found to be intrinsically correlated with the width of the water body and the shape of the river bank. Fei et al [11] took the thermal environment of waterfront spaces in Tianjin as their research object, and through a quantitative analysis of the microclimate of four typical waterfront spaces in Tianjin, it was found that the most economical water body width was 70-80 m, and that the cooling effect of a water body was able to be significantly improved when the geometry of a given water body along the shoreline was in the form of an S shape. Similarly, Hongyu et al [12] found that the cooling provided by a body of water can vary according to its geometry, with lakes exhibiting greater cooling than rivers.…”
Section: Literature Review 21 Cooling Effect Of Water Bodiesmentioning
confidence: 99%
“…A healthy city is one that continually creates and improves its physical and social environments and expands community resources to enable people to mutually support each other. Previous studies of built environments have suggested that blue-green spaces, which are composed mainly of plants and water resources, are an important carrier Land 2023, 12,1929 2 of 13 of a healthy city as they contribute to a landsense ecology in sustainable cities [10]. Urban forested areas near water also play a potential role in healthy cities as they generally have similar compositions to blue-green spaces, which suggests that we should pay more attention to these areas.…”
Section: Introductionmentioning
confidence: 99%
“…The location of urban forests can influence the diversity of animal species. For example, in urban downtown areas, urban forests by the riverside perform the same function as an urban waterfront park [12]. Pets are animals that often accompany their owners during recreational activities in urban downtown areas, which suggests a lack of terrestrial wildlife in urban environments [13].…”
Section: Introductionmentioning
confidence: 99%